Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature